MODEL PEMBELAJARAN PAI BAGI PENYANDANG TUNAGRAHITA DI SMP LUAR BIASA TAMAN RAFLESIA CIKONENG KABUPATEN CIAMIS - Nurmala, Eneng; Azis, Abdul; Selamet, Selamet (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2015)
This research was conducted to determine the PAI learning model for people with intellectual disabilities in Extraordinary Middle School Taman Raflesia Cikoneg Ciamis. The results showed that: 1) SMPLB Taman Raflesia Cikoneng Ciamis regency more often uses quantum learning models and adaptive learning models in PAI subjects on mentally disabled students, using lecture methods, question and answer methods, exemplary methods, habituation methods and demonstration methods; 2) The learning process of Islamic Religious Education (PAI) at SMPLB Taman Raflesia Cikoneng is united between classes VII, VIII, IX. The steps of the learning process are divided into three activities, namely: Initial activities, core activities, and closing activities; 3) Achievement of mentally retarded students at the Raflesia Park in the subjects of Islamic Religion is quite encouraging by obtaining an average score of 78.6, which means very good, even though mentally retarded students possess limitations in intelligence functions which are below average but their achievements are equal to other normal students. This can be seen from the results of learning evaluation scores above the KKM standard.